ELTROXIN LIKE MIMIC ACTION OF WITHANIA SOMNIFERA LEAF EXTRACT IN HYPOTHYROID-INDUCED RATS - Purohit, Abhilasha; Purohit, Ashok (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was designed to examine the anti-hypothyroid activity of Withania somnifera (Ashwagandha)'s leaf extract on 6-n-propyl- 2-thio-uracil (PTU) induced hypothyroid rats. Method: Ethanolic extracts of W. somnifera leaf and Eltroxin were administrated to PTU induced hypothyroid rats. The animals were divided into control, PTU treatment, W. somnifera leaf extract treatment, and Eltroxin treatment groups for 60 days. The serum T3 and T4 were estimated, and biochemical and hematological parameters of the blood serum were also evaluated. Results: PTU induction caused a significant decrease (pâ‰¤0.001) in T3 and T4 level when compared with the control group. Adverse effects of PTU were also observed in blood sugar, cholesterol, alkaline phosphate, protein, albumin, globulin, liver function test, and renal function test parameters. Non-significant changes in LFT,RFT and Other parameters were observed. W.Somnifera's leaf extract and Eltroxin treatment group recovered both of the thyroid hormone secretion as compare to control.